2007
DOI: 10.1002/pd.1647
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific risk of fetal loss post second trimester amniocentesis: analysis of 5043 cases

Abstract: No effect of the 2nd trimester amniocentesis was noted on fetal loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(19 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…The risk for Brought to you by | University of Iowa Libraries Authenticated Download Date | 6/3/15 11:30 AM fetal loss was no different among the operators, because all five were experienced. These results are in accordance with the published data of previous studies [9,[21][22][23][24].…”
Section: Discussionsupporting
confidence: 96%
“…The risk for Brought to you by | University of Iowa Libraries Authenticated Download Date | 6/3/15 11:30 AM fetal loss was no different among the operators, because all five were experienced. These results are in accordance with the published data of previous studies [9,[21][22][23][24].…”
Section: Discussionsupporting
confidence: 96%
“…12 Chorionic villus sampling procedure-related loss rates are similar to amniocentesis when performed in experienced centers. 13 If a false-negative result occurs, some may say that the families who had undergone testing are no worse off for having a screening test for a rare condition.…”
Section: Financial Disclosurementioning
confidence: 75%
“…15,27 In the same way maternal age and abnormal maternal serum a fetoprotein measurements increase the risk for pregnancy loss. 19,[28][29][30][31] Vaginal bleeding during current pregnancy increase the risk of spontaneous abortion and pregnancy loss after amniocentesis in most of the series. 29 In our recent series, we also found that bleeding during first and early second trimester of current pregnancy increase the risk of pregnancy loss after amniocentesis by two to three times.…”
Section: 10 Fetal Lossmentioning
confidence: 99%